Recombination Events and Conserved Nature of Receptor Binding Motifs in Coxsackievirus A9 Isolates - Eero Hietanen; Petri Susi (MDPI AG, 2022)
Coxsackievirus A9 (CVA9) is an enterically transmitted enterovirus and one of the most pathogenic type among human enteroviruses. CVA9 isolates use a distinctive RGD (Arg-Gly-Asp) motif within VP1 capsid protein that defines its ability to bind to integrin receptor(s) for cellular entry. To investigate CVA9 evolution and pathogenicity, genetic relationships and recombination events were analyzed between 54 novel clinical isolates of CVA9, as well as 21 previously published full length CVA9 sequences from GenBank. Samples were investigated by partial sequencing of the novel VP1 and 3Dpol genes, as well as including the corresponding areas from GenBank sequences. Phylogenetic analyses were combined with clinical data in a further attempt to analyze whether sequence evolution reflects CVA9 pathogenicity in the phylogenies. Furthermore, VP1 gene was also analyzed for receptor binding sites including the RGD motif and the putative heparan sulfate (HS) site. Analysis of the 559-nucleotide-long VP1 sequences identified six clades. Although most of the strains within each clade showed geographical clustering, the grouping pattern of the isolates in the analysis of the VP1 gene was strikingly different from grouping of 3Dpol, which suggests that recombination events may have occurred in the region encoding the nonstructural proteins. Inclusion of clinical data did not provide any evidence of symptom based phylogenetic clustering of CVA9 isolates. Amino acid sequence analysis of the VP1 polypeptide demonstrated that the RGD motif was fully conserved among the isolates while the putative HS binding site was only found in one isolate. These data suggest that integrin binding is essential for virus tropism, but do not explain the symptom repertoire.